Subclinical amnionitis in patients with intact membranes in preterm labour - Guvenc, Muzehher; Guvenc, Huseyin; Cengiz, Lugen; Cengiz, Tevfik; Uslu, Turhan (My University, 1989)
Summary. Preterm delivery is the major obstetric and paediatric problem, being responsible for much perinatal morbidity and mortality. Subclinical amnionitis may cause preterm labour and delivery. The rate of subclinical bacterial infection of amniotic fluid was studied in 25 afebrile pregnant women with intact membranes in preterm labour. Specimens of amniotic fluid were collected by transabdominal amniocentesis. Serum and amniotic fluid lactic dehydrogenase (LDH) levels were assessed to determine their usefulness in making the diagnosis of subclinical amnionitis. Aerobic bacteria were isolated from 48% (12/25) of the specimens. Thus, subclinical amnionitis may play a substantial role in patients with intact membranes in preterm labour. However, transabdominal amniocentesis is not routinely indicated in similar asymptomatic patients because microbiological and especially LDH studies require further evaluation. Copyright © 1989, Wiley Blackwell. All rights reserved
Keywords: Amniotic Fluid; Bacteria; Bacteriological Techniques; Chorioamnionitis; Female; Fetal Membranes, Premature Rupture; Human; Infant, Newborn; Labor, Premature; Lactate Dehydrogenase; Pregnancy; lactate dehydrogenase; amnionitis; bacterial infection; female; human; pregnancy; prematurity; short survey